Closing the gender gap in STEM with friendly male instructors? On the effects of rapport behavior and gender of a virtual agent in an instructional interaction. (August 2016) - Krämer, Nicole C.; Karacora, Bilge; Lucas, Gale; Dehghani, Morteza; Rüther, Gina; Gratch, Jonathan
Abstract: While numerous research endeavors address the effects of pedagogical agents, the role of the agent's gender and its rapport behavior has been neglected. We hypothesize that a minimal amount of behavioral realism induced by display of rapport is necessary for any social effects to occur in human-computer interaction. Further, in line with results from STEM research on female role models, we assume that especially for female learners a same sex agent will be beneficial. In a 2 (student gender) × 2 (agent gender) × 2 (rapport behavior yes/no) between subjects design, we investigate whether virtual agents can help enhance participants' performance, effort and motivation in mathematics. Female and male participants (N = 128) interacted with a male or female virtual agent that either displayed rapport or no rapport. Our results confirm the expected main effect of rapport. However, against expectations, our results do not support the assumption that a same sex agent is beneficial for female learners. Participants' performance and effort were significantly enhanced when interacting with an agent of opposite gender that displayed rapport. Our results have implications on designing agents for education and training purposes. Highlights: A virtual agent most successfully supports learning when it shows rapport behavior. Although participants do not perceive increased rapport, the agent displaying rapport fosters performance. A virtual agent of opposing gender, not same sex, is most successful in fostering participants' performance.